Lorenzo Ruiz [videorecording] - O'hara, Mario (Communication Foundation for Asia, 1980)
The story of a lowly escribano from Binondo who was martyred in Japan in 1637 and who became the first Filipino to be beatified by the Roman Catholic church in rites performed by Pope John Paul II in Manila in 1981.